Analisis Pemeriksaan Dan Perawatan Dinding Terowongan MRT Jakarta - Astuti, Septiana Widi; Atmaja, Dadang Sanjaya; Waskito, Ario (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
Tunnel construction in the Jakarta MRT (MRTJ) is a concrete tunnel that was built using the Tunnel Boring Machine (TBM) drill machine. Tunnel walls in underground construction use pre-cast (segment) concrete materials arranged in a circle directly into one ring segment by TBM. Tunnel checks are needed to be the basis of diagnosis in tunnel care. Tunnel maintenance is carried out to maintain the condition of the tunnel to function properly and safely to be operated in a sustainable manner in accordance with the predicted load, including: the burden of soil or overburden, dead load and live load, load due to water pressure, earthquake load, and other loads that will affect tunnel construction. The results of the study that damage to the tunnel wall can be classified as leaks and cracks. Examination of components in the MRTJ tunnel wall by paying attention to the detail part of the wall in the form of segment bolts, connections between segments, concrete structures in segments. As for the maintenance carried out to repair and prevent tunnel wall leaks, it can be done by grouting polyurethane liquids and replacing rubber sealing on the bolts, for treatment due to cracks can be done by grouting liquid microscopy and plastering.